EU–China paradiplomacy – the perspective of cities, regions and provinces - Skorupska, Adriana; Szczudlik, Justyna (The Role of Regions in EU-China Relations, 2021)
The main goal of this chapter is to present some characteristics of the cooperation at the regional level from the European local government perspective, including the Chinese attitude to the matter in question. The chapter starts with some basic information about the methodology and the course of the research. Next the two perspectives are presented. The first one will be the characteristics of EU-China paradiplomacy based on the data from the questionnaire completed by the regions and selected cities from the six biggest European Union countries. The second perspective focuses on the paradiplomatic phenomena from the Chinese perspective. The chapter finishes with some conclusions about the EU-China paradiplomacy and general observations.